Gender and age significantly determine patient needs and treatment goals in psoriasis – a lesson for practice. (15th January 2019) - Maul, J.‐T.; Navarini, A.A.; Sommer, R.; Anzengruber, F.; Sorbe, C.; Mrowietz, U.; Drach, M.; Blome, C.; Boehncke, W.‐H.; Thaci, D.; Reich, K.; von Kiedrowski, R.; et al.
Abstract: Background: Though patient needs are key drivers of treatment decisions, they are rarely systematically investigated in routine care. Objective: This study aimed at analysing needs and expectations from the patient perspective in the German and Swiss psoriasis registries PsoBest and Swiss Dermatology Network of Targeted Therapies (SDNTT) with respect to treatment choice, age and gender. Methods: The German and Swiss psoriasis registries observe patients recruited at first‐time use of systemic drugs. Within 10 years, clinical [Psoriasis Area Severity Index (PASI), Body Surface Area (BSA)] and patient‐reported outcomes are documented, including the Dermatology Quality of Life Index (DLQI) and the Patient Benefit Index (PBI), characterizing patient needs for treatment. The analysis data set includes n  = 4894 patients from PsoBest and n  = 449 from SDNTT with mean follow‐up time of 7.5 months. Results: A total of 5343 patients registered between 2008 and 2016 were included in the analyses (at baseline: 59.6% male, mean age 47.6 years ± 14.5, PASI 14.2 ± 9.7, BSA 22.7 ± 19.7, DLQI 11.3 ± 7.2). The most important patient needs were to 'get better skin quickly' and to 'be healed of all skin defects'. Subgroup analyses by age revealed significant differences in needs, especially higher needs regarding social impairments in patients younger than 65 years. Patients 65 years or older attributed more importance to sleep quality, less dependency on medical visits, fewer side‐effects and confidence in the therapy. Out of 25 items reflecting patient needs, 20 items were rated significantly more important by women than men, with the greatest differences regarding feeling of depression, sleep quality and everyday productivity. Divided by treatment, needs were rated differently, recommending individualized and targeted choice of therapy. Conclusion: Age and gender stratify patient needs. Women showed higher expectations and rated specific needs in psoriasis treatment higher than men. Analysing the patient needs on an individual level will facilitate shared decisions by patient and physician in finding the optimal personalized treatment.